Analysis of the Attitudes towards Sexuality in People with Intellectual Disabilities: A Cross-Sectional Study - José Carlos López-García; Azucena González-Sanz; Elena Sutil-Rodríguez; Carlos Saus-Ortega; Regina Ruiz de Viñaspre-Hernádez; Raúl Juárez-Vela; Vicente Gea-Caballero; Juan Luis Sánchez-González; Clara Isabel Tejada-Garrido; Ana Cobos-Rincón; José María Criado-Gutiérrez; Consuelo Sancho-Sanchez (MDPI AG, 2023)
The barriers faced by people with intellectual disabilities are many. One of the areas in which many problems have been identified is the sexual domain. This descriptive study aims to analyze the attitudes of the family environment, professional carers, and the general population toward their sexuality. A cross-sectional descriptive study was carried out between 2022 and 2023, using convenience sampling among family members and carers from different centers working with people with intellectual disabilities in Spain, and among the general population not related to people with intellectual disabilities. A total of 583 responses were received and significant differences were found for all variables, with the variables related to family or work proximity being those that provided the most significant and relevant results. It was observed that the male sex has a more paternalistic attitude and that in rural areas there is a more permissive attitude towards the sexuality of people with intellectual disabilities. People who work with people with disabilities have more positive attitudes towards this group, while direct relatives have more paternalistic attitudes. Nursing care in the community and specialized centers should be based on an adequate therapeutic relationship and personalized care.